PENGARUH TIPE PEMISAHAN TERHADAP PENYALURAN PEMBIAYAAN PADA BANK UMUM SYARIAH HASIL PEMISAHAN - Al Arif, M Nur Rianto (JURNAL EKONOMI DAN BISNIS ISLAM, 2016)
The Islamic business unit spinoff has taken two forms such as pure spinoff and spinoff withacquisition, convert, and merger. The objective of this research is to analyze the impact ofspinoff type to financing in spinoffs banks. The analysis technique that used in this paper ispanel regression with random effect model. The result shows that the spinoff type didn?t havean influence to financing in spinoffs banks. The implication of this result is the spinoffs typedecision depend on business consideration that the most useful and practice.